EPIGENETIC BASIS OF INFERTILITY IN YOUNG MEN AND ITS IMPACT ON THE HEALTH OF FUTURE GENERATIONS (Western European Journal of Medicine and Medical Science, 2025)
The epigenetic mechanisms of male infertility in young men have recently become the focus of scientific research. In addition to genetic factors, processes such as DNA methylation, histone modification, and microRNA expression significantly regulate spermatogenesis. This article analyzes the epigenetic basis of male infertility, its heritability, and its impact on the health of future generations. The findings indicate that epigenetic alterations may not only cause infertility but also influence the development of hereditary diseases in offspring